2019
DOI: 10.5977/jkasne.2019.25.4.508
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Jigsaw Cooperation Learning on Communication Ability, Problem Solving Ability, Critical Thinking Disposition, Self-directed Learning Ability and Cooperation of Nursing Students

Abstract: Purpose: This study was conducted to examine the effects of jigsaw cooperative learning on the communication ability, problem solving ability, critical thinking disposition, self-directed learning ability and cooperation of nursing students. Methods: A one-group, pre-post design was utilized with 92 nursing students as subjects. The data were analyzed using descriptive statistics and paired t-tests using SPSS/WIN 24.0. Results: The scores on problem solving ability, self-directed learning ability and cooperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Collaborative learning experiences that enable group members to interact together and learn with and from each other are mainly involved in the good functioning of SDL in work-integrated learning settings (Schrode et al, 2021). Recent studies showed that group cooperation improves problem-solving and self-directed learning abilities (Kim & Kim, 2019;Wang et al, 2021). With regard to the influence of the teachers' collegial cooperation on the use of ICT in the classroom, the findings so far point to the fact that teamwork can bring up further development of competence in e-teaching.…”
Section: The Role Of Collegial Cooperation In Sdlmentioning
confidence: 99%
“…Collaborative learning experiences that enable group members to interact together and learn with and from each other are mainly involved in the good functioning of SDL in work-integrated learning settings (Schrode et al, 2021). Recent studies showed that group cooperation improves problem-solving and self-directed learning abilities (Kim & Kim, 2019;Wang et al, 2021). With regard to the influence of the teachers' collegial cooperation on the use of ICT in the classroom, the findings so far point to the fact that teamwork can bring up further development of competence in e-teaching.…”
Section: The Role Of Collegial Cooperation In Sdlmentioning
confidence: 99%